America's battlegrounds : walk in the footsteps of America's bravest - Sauers, Richard Allen (Reader's Digest Association, 2005)
Historical photographs, maps, illustrations, and documents provide information on battlefield sites within the national park system that commemorate the battles that shaped the country.